2022
DOI: 10.1088/1755-1315/1018/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

The potency of Vis/NIR spectroscopy for classification of soybean based of colour

Abstract: Soybean in various colour is easy to identify using human eyes. However, it is hard to perform manual method for on-line production. Therefore, detection of colour for sorting the soybean is important especially for industries which require a rapid and real-time task. This research was conducted to study the potency of a modular type of VIS/NIR spectroscopy at wavelength of 350-1000 nm to classify black, green, and yellow of soybean seed and flour. Principal component analysis (PCA) and PCA Linear discriminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Longoni et al (2020) and Gebregziabher et al (2022) reported chlorophyll and carotenes substances in the visible range, where R 2 values in calibration and prediction played a significant role in specific sample classification. At 680 nm, soybean samples showed chlorophyll content that distinguished green color (Pahlawan et al (2022). In the visible range, the absorption peaks of chlorophyll-a occur at 430 nm and 662 nm, while chlorophyll-b was found at 453 nm and 642 nm ( Lopes et al 2017;Shi et al 2022;Yang et al 2022;Zhu et al 2018).…”
Section: Partial Least Square Regression (Plsr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Longoni et al (2020) and Gebregziabher et al (2022) reported chlorophyll and carotenes substances in the visible range, where R 2 values in calibration and prediction played a significant role in specific sample classification. At 680 nm, soybean samples showed chlorophyll content that distinguished green color (Pahlawan et al (2022). In the visible range, the absorption peaks of chlorophyll-a occur at 430 nm and 662 nm, while chlorophyll-b was found at 453 nm and 642 nm ( Lopes et al 2017;Shi et al 2022;Yang et al 2022;Zhu et al 2018).…”
Section: Partial Least Square Regression (Plsr)mentioning
confidence: 99%
“…Peak in absorbance of around 670 nm found in the olive oil spectrum confirmed the presence of chlorophyll pigments (Lapčíková et al 2018). At 500 nm, soybean samples indicated carotenoid content that distinguished yellow or darker (Pahlawan et al 2022).…”
Section: Partial Least Square Regression (Plsr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical techniques are used to extract information from the spectra. Vis/NIR spectroscopy is a non-destructive technique used to measure quality attributes of fruits and vegetables [4].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a Vis-NIR spectroscopy working at the wavelength of 350 -1000 nm is affordable and has been used to predict the contents of lycopene and carotene in tomatoes [21] or chlorophyl in apples [22]. The portable type of Vis-NIR spectrometer is cheap and suitable for the quality [23,24] and quantity detection [25,26] of agricultural products. However, the use of a Vis-NIR spectroscopy for the quantification of phytochemicals in red beet has not been studied.…”
Section: Introductionmentioning
confidence: 99%